International Guests: Opening Pathways and Weaving Nets (2010)
Jorge Wagensberg, physicist and founder of CosmoCaixa, the Science Museum in Barcelona, met the children participating in EAFIT Children's University. Why was school invented? This researcher was invited to give a lecture about Intellectual joy, a theory of his that has nurtured the methodology of EAFIT Children's University.